Development of Biarylalkyl Carboxylic Acid Amides with Improved Anti‐schistosomal Activity. (18th September 2019) - Peter Ventura, Alejandra M.; Haeberlein, Simone; Lange‐Grünweller, Kerstin; Grünweller, Arnold; Hartmann, Roland K.; Grevelding, Christoph G.; Schlitzer, Martin
Abstract: The parasitic disease schistosomiasis is the cause of more than 200 000 human deaths per year. Although the disease is treatable, there is one major shortcoming: praziquantel has been the only drug used to combat these parasites since 1977. The risk of the emergence of resistant schistosomes is known to be increasing, as a reduced sensitivity of these parasites toward praziquantel has been observed. We developed a new class of substances, which are derived from inhibitors of human aldose reductase, and which showed promising activity against Schistosoma mansoni couples in vitro. Further optimisation of the compounds led to an increase in anti‐schistosomal activity with observed phenotypes such as reduced egg production, vitality, and motility as well as tegumental damage and gut dilatation. Here, we performed structure–activity relationship studies on the carboxylic acid moiety of biarylalkyl carboxylic acids. Out of 82 carboxylic acid amides, we identified 10 compounds that are active against S. mansoni at 25 μm . The best five compounds showed an anti‐schistosomal activity up to 10 μm and induced severe phenotypes. Cytotoxicity tests in human cell lines showed that two derivatives had no cytotoxicity at 50 or 100 μm . These compounds are promising candidates for further optimisation toward the new anti‐schistosomal agents. Abstract : No flukes with these amides ! Schistosomiasis causes more than 200 000 deaths per year and is treated with the single drug praziquantel. We have previously reported biarylalkyl carboxylic acid derivatives as novel chemical entities with in vitro anti‐schistosomal activity. In continuation of these studies, we report here a series of amide derivatives. The best results were obtained with morpholine, thiomorpholine and substituted piperazine derivatives.